Impacts of project team and innovation process on new product development. (1st January 2011) - Chan, S.L.; Ip, W.H.; Chung, Roy C.P.
An exploratory model of the innovation process, project team and new product success is presented in this paper. The construct of the innovation process includes eight items, that of the project team includes five, and that of the new product success contains three. These items measured in the survey are regarded as the outcomes, rather than the attributes, of the three constructs. An interesting finding is that the perspectives of managers at different levels on which of these outcomes are more important to innovation differ significantly. Our findings provide managers with evidence that allows them to concentrate on more important outcomes which should be achieved for better innovation. The results also indicate that the project team is an important enabler in the innovation process, while the innovation process has a significant impact on new product success. Effective communication and technical competence/talent are found to be the two most important innovation outcomes that firms should attain.